2006
DOI: 10.1016/j.tplants.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

AOX – a functional marker for efficient cell reprogramming under stress?

Abstract: Functional markers for stress tolerance can be used in plant breeding to identify genotypes with high yield stabilities under various conditions. Thus, a good marker should show a strong correlation with favourable adaptive plant behaviour. The efficient reprogramming of target cells for yield determination is currently considered to be the most important step towards defining abiotic stress tolerance. In this Opinion article, we propose a role for the alternative oxidase (AOX) gene as a marker for genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
140
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 56 publications
7
140
0
1
Order By: Relevance
“…Siedow and his colleagues suggested that AOX affects the metabolism through more pervasive effects, including some that are extramitochondrial Umbach et al, 2005). They further proposed an idea that the Aox gene functions, as a marker for genetic variation in cell reprogramming, yield stability and stress resistance (Arnholdt-Schmitt et al, 2006). In our experiment, the AOX protein level, mRNA level, and cyanide-resistant respiration are tightly correlated with Cd stress resistance, varying among the different wheat cultivars.…”
Section: Discussionsupporting
confidence: 49%
“…Siedow and his colleagues suggested that AOX affects the metabolism through more pervasive effects, including some that are extramitochondrial Umbach et al, 2005). They further proposed an idea that the Aox gene functions, as a marker for genetic variation in cell reprogramming, yield stability and stress resistance (Arnholdt-Schmitt et al, 2006). In our experiment, the AOX protein level, mRNA level, and cyanide-resistant respiration are tightly correlated with Cd stress resistance, varying among the different wheat cultivars.…”
Section: Discussionsupporting
confidence: 49%
“…Siedow and his colleagues suggested that CN-resistant respiration affected the metabolism through more pervasive effects, including some that were extramitochondrial Umbach et al 2005). They further proposed an idea that the CN-resistant respiration, as a marker for genetic variation in cell reprogramming, yielded stability and stress resistance (Arnholdt-Schmitt et al 2006). In our study, HA63 had the highest rates of CN-resistant respiration after the Cd stress, while S8258 had the lowest rates, which is consistent with their level of Cd tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, not only would AOX act as a terminal oxidase, but it would also initiate cellular reprogramming appropriate to the environmental situation . It is for this reason that AOX has been suggested as a possible genetic marker that could be used to recognise that efficient cellular reprogramming is taking place during exposure to a given stress (Arnholdt-Schmitt et al 2006).…”
Section: Role In Cellular Reprogrammingmentioning
confidence: 99%